Effect of foot type on knee valgus, ground reaction force, and hip muscle activation in female soccer players - Rath, M. E.; Stearne, D. J.; Walker, C. R.; Cox, J. G. (The Journal of Sports Medicine and Physical Fitness, 2016)
BACKGROUND: The purpose of this study was to determine the degree to which subtalar joint pronation resulting from a supple planus foot affects knee alignment, hip muscle activation and ground reaction force attenuation in female athletes during a broad jump-to-cut maneuver.